Aortic diameter at age 65 in men with newly diagnosed type 2 diabetes. (4th July 2017) - Taimour, Soumia; Zarrouk, Moncef; Holst, Jan; Rosengren, Anders H.; Groop, Leif; Nilsson, Peter M.; Gottsäter, Anders
Abstract: Objectives. Type 2 diabetes mellitus has been linked to a decreased risk for abdominal aortic aneurysm (aortic diameter ≥30 mm, AAA) development in men. The aim of this study was to evaluate if such an effect is detectable already around the time of diabetes diagnosis. Design. We cross-sectionally compared aortic diameter at ultrasound screening for AAA in 691 men aged 65 years with incipient or newly diagnosed type 2 diabetes (group A) with 18, 262 65-year old control men without diabetes (group B). Results. Aortic diameter did not differ between groups (18.8[17.4–20.8] vs. 19.0[17.5–28.7] mm; p = 0.43). AAA prevalence was 2.5% in group A and 1.5% in group B (p = .010). In logistic regression taking group differences in body mass index (BMI), smoking, presence of atherosclerotic disease and hypertension into account, the difference in AAA prevalence was no longer significant (p = .15). Among men in group A, C-peptide (r = .093; p = .034), but not HbA1c (r = .060; p = .24) correlated with aortic diameter. Conclusion. Among 65 year old men aortic diameter and AAA prevalence do not differ between those with newly diagnosed type 2 diabetes and those without diabetes. Putative protective effects of type 2 diabetes mellitus against aortic dilatation and AAA development therefore probably occur later after diagnosis of diabetes.